ASSESSING FUNCTIONAL OUTCOMES OF VARIOUS TREATMENTS FOR INTRA-ARTICULAR FRACTURES OF THE DISTAL RADIUS IN ADULTS, BHAGALPUR, INDIA: A RETROSPECTIVE CROSS-SECTIONAL STUDY. - Bhagat, Uday Shankar; Saurabh, Shanu (Student’s Journal of Health Research Africa, 2024)
Background Assessing the functional outcomes of various treatments for intra-articular fractures (IAF) of the distal radius in adults is crucial for optimizing patient care and recovery. The study objective was to estimate and compare the functional results of different treatment modalities utilized for IAF of the distal end of the radius in adult patients. Methods The retrospective study comprised a total of 80 adult patients. Data on demographic characteristics, fracture type, treatment modalities, postoperative complications, radiological outcomes, pain scores, and functional scores were gathered from medical records. Statistical analysis was accomplished using STATA-17 software. Results Among the 80 patients, 50% opted for conservative management, while the remaining 50% underwent surgical intervention, including pinning, external fixation, or plating. Surgical intervention was related to better functional outcomes compared to conservative management, with significant differences observed in functional scores (p < 0.05). However, no significant variation was recorded in pain scores among the two groups. Postoperative complications were observed in 22.5% of patients, predominantly in the plating group. Radiological union was achieved in the majority of cases, with a small percentage experiencing nonunion or residual deformities. Conclusion Surgical intervention, particularly pinning, external fixation, and plating, demonstrated superior functional outcomes compared to conservative management for IAF of the distal radius. Patient education and rehabilitation play crucial roles in enhancing functional recovery and compliance with postoperative protocols. Recommendations Surgeons should carefully select the appropriate surgical technique based on fracture characteristics and patient factors to optimize outcomes and minimize complications. However, the choice of surgical technique should be carefully considered to minimize postoperative complications and residual deformities. Emphasis should be placed on patient education and rehabilitation to ensure compliance with postoperative protocols and enhance functional recovery.